Integrated pest management system using fuzzy expert system - Siraj, Fadzilah; Arbaiy, Nureize (Universiti Utara Malaysia, 2006)
Knowledge and information related to all aspects of crop-pest system are the foundations on which modern pest management decisions are based. The transfer of research and extension information to farmers plays the key role in the adoption of integrated pest management (IPM). FuzzyXPest is proposed to provide information to the farmers and researchers using fuzzy expert system. Since rice is the main staples food of the Malaysian and Kedah is known as 'rice bowl' Malaysia, therefore this study focuses on the pest's activity in the rice field. In FuzzyXPest,the type of pest that canses damage to the rice plant is determined by the expert system. Fuzzy Logic approach is then used to forecast the pest activity level that will determining the pest activity level is imperfect,fuzzy logic is used to cater for the uncertainty of information. The system has been verified by Malaysia Agriculture Research and Development Institute (MARDI) entomologist and the system is confirmed to benefit the researchers at MARDI and Department of Agriculture (DOA) particularly, and the farmers at large.